2003
DOI: 10.1128/aem.69.12.7527-7530.2003
|View full text |Cite
|
Sign up to set email alerts
|

Chemoattraction of Vibrio fischeri to Serine, Nucleosides, and N -Acetylneuraminic Acid, a Component of Squid Light-Organ Mucus

Abstract: Newly hatched juveniles of the Hawaiian squid Euprymna scolopes rapidly become colonized by the bioluminescent marine bacterium Vibrio fischeri. Motility is required to establish the symbiotic colonization, but the role of chemotaxis is unknown. In this study we analyzed chemotaxis of V. fischeri to a number of potential attractants. The bacterium migrated toward serine and most sugars tested. V. fischeri also exhibited the unusual ability to migrate to nucleosides and nucleotides as well as to N-acetylneurami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 15 publications
2
79
0
Order By: Relevance
“…Marine bacteria have been shown to exhibit chemotaxis towards carbohydrates present in the exudates of phytoplankton (Hellebust, 1965;Bell and Mitchell, 1972) and in the mucus of the Hawaiian squid Euprymna scolopes light organ (DeLoney-Marino et al, 2003). Despite the prominence of carbohydrates in coral mucus (Ducklow and Mitchell, 1979b;Meikle et al, 1988;Wild et al, 2005), the chemotactic response of coral-associated bacteria towards the tested carbohydrates in both the syringe assays and the ISCAs were never significantly different from the FSW control.…”
Section: Sandy Substratementioning
confidence: 92%
“…Marine bacteria have been shown to exhibit chemotaxis towards carbohydrates present in the exudates of phytoplankton (Hellebust, 1965;Bell and Mitchell, 1972) and in the mucus of the Hawaiian squid Euprymna scolopes light organ (DeLoney-Marino et al, 2003). Despite the prominence of carbohydrates in coral mucus (Ducklow and Mitchell, 1979b;Meikle et al, 1988;Wild et al, 2005), the chemotactic response of coral-associated bacteria towards the tested carbohydrates in both the syringe assays and the ISCAs were never significantly different from the FSW control.…”
Section: Sandy Substratementioning
confidence: 92%
“…Among squid symbionts, nine of these MCP genes are specific to strain ES114 and, therefore, are unlikely to be critical for colonization; however, it is possible that their functions are compensated by non-homologous members of the other strains' MCP repertoires, thereby complicating any inference of their importance in light-organ colonization. Although some chemoattractants of V. fischeri have been identified, the specific ligands of the MCPs present in V. fischeri are known for only three (DeLoney-Marino et al, 2003;Brennan et al, 2013;Nikolakakis et al, 2015), none of which is required for light-organ colonization.…”
Section: Mauve-gene Distributionmentioning
confidence: 99%
“…Several culturedependent and -independent studies have confirmed the ubiquity of vibrios, and suggested Vibrio populations generally comprise approximately 1% (by molecular techniques) of the total bacterioplankton in estuaries (19), in contrast to culture-based studies demonstrating that vibrios can comprise up to 10% of culturable marine bacteria (20). Clearly, vibrios are ubiquitous and abundant in the aquatic environment on a global scale, including both seawater and sediment (19,(21)(22)(23)(24)(25), and repeatedly shown to be present in high densities in and on marine organisms, such as corals (26), fish (27-29), mollusks (30), seagrass, sponges, shrimp (28, 31), and zooplankton (16,17,28,32,33).…”
mentioning
confidence: 99%
“…Several culturedependent and -independent studies have confirmed the ubiquity of vibrios, and suggested Vibrio populations generally comprise approximately 1% (by molecular techniques) of the total bacterioplankton in estuaries (19), in contrast to culture-based studies demonstrating that vibrios can comprise up to 10% of culturable marine bacteria (20). Clearly, vibrios are ubiquitous and abundant in the aquatic environment on a global scale, including both seawater and sediment (19,(21)(22)(23)(24)(25), and repeatedly shown to be present in high densities in and on marine organisms, such as corals (26), fish (27-29), mollusks (30), seagrass, sponges, shrimp (28, 31), and zooplankton (16,17,28,32,33).During dives of the deep-sea submersibles Alvin and Nautile in 1999 along the East Pacific Rise, southwest of the Mexico coast, samples of water surrounding sulfide chimneys of a hydrothermal vent community were collected and four mesophilic bacterial isolates were cultured, which were subsequently tested for phenotypic traits, including growth on V. cholerae selective thiosulfate-citrate-bile-salts-sucrose (TCBS) agar (Oxoid). The sampling locations from where these four mesophilic bacteria were isolated are described in Table 1.…”
mentioning
confidence: 99%